2010
DOI: 10.1007/s10495-010-0521-9
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors synergistically potentiate death receptor 4-mediated apoptotic cell death of human T-cell acute lymphoblastic leukemia cells

Abstract: Cell-death signaling through the pro-apoptotic tumor necrosis factor-related apoptosis inducing ligand (TRAIL) receptors, death receptor 4 (DR4) and DR5, has shown tumor-selective apoptotic activity. Here, we examine susceptibility of various leukemia cell lines (HL-60, U937, K562, CCRF-CEM, CEM-CM3, and THP-1) to an anti-DR4 agonistic monoclonal antibody (mAb), AY4, in comparison with TRAIL. While most of the leukemia cell lines were intrinsically resistant to AY4 or TRAIL alone, the two T-cell acute lymphobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…The combination regimen also induced the expression of BAX, an apoptosis-related protein, in THP-1 cells. Moreover, it is known that treatment with HDAC inhibitors promotes BAX-dependent apoptosis in several cell types (24,25). In the present study, we showed that BAX also plays critical roles in Ara-C and VPA-induced apoptosis in AML cells.…”
Section: Discussionsupporting
confidence: 61%
“…The combination regimen also induced the expression of BAX, an apoptosis-related protein, in THP-1 cells. Moreover, it is known that treatment with HDAC inhibitors promotes BAX-dependent apoptosis in several cell types (24,25). In the present study, we showed that BAX also plays critical roles in Ara-C and VPA-induced apoptosis in AML cells.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, we (and others) have demonstrated that HDACi action is indeed tumor selective, impacting on proapoptotic pathways in cancer but not in normal cells (12,44). Specifically, our and other groups have shown that HDACi-induced cancer-selective apoptosis involves TRAIL reexpression in AMLs (12,45).…”
Section: Discussionmentioning
confidence: 68%
“…Cell Lines and Reagents-Human cervical carcinoma HeLa cells were purchased from the ATCC (Manassas, VA) and grown in DMEM supplemented with 10% (v/v) FCS, 100 units/ml penicillin, and 100 g/ml streptomycin (Invitrogen) as described previously (18,19). RFK-deficient HeLa shRFK cells that stably express RFK-specific shRNA (14) were a kind gift from Prof. Martin Krönke (University of Cologne) and were grown in the same conditions with wild type HeLa cells.…”
Section: Methodsmentioning
confidence: 99%